Basic christological distinctions - Wildman, Wesley J. (Theology today, 2007)
This essay surveys major distinctions used to classify and gain insight into contemporary christologies, clarifying some confusions about them. The focus is on distinctions pertaining to christological starting points (from above, form below), schemas (cosmological, anthropological, eschatological, dialectical), styles ( historical versus ideal, ontological versus functional), and results (high versus low, literally and figuratively incarnational, absolutist and anti-absolutist or modest). The essay concludes with an argument that the absolutist-modest distinction helps to diagnose several important fault lines in contemporary christology.